How Do Individuals with Persecutory Delusions Bring Worry to a Close? An Interpretive Phenomenological Analysis - Startup, Helen; Pugh, Katherine; Cordwell, Jacinta; Kingdon, David; Freeman, Daniel (Behavioural and cognitive psychotherapy, 2015)
Background: Worry is a significant problem for individuals with paranoia, leading to delusion persistence and greater levels of distress. There are established theories concerning processes that maintain worry but little has been documented regarding what brings worry to a close. Aims: The aim was to find out what patients with persecutory delusions report are the factors that bring a worry episode to an end. Method: Eight patients with persecutory delusions who reported high levels of worry participated. An open-ended semi-structured interview technique and IPA qualitative analysis was employed to encourage a broad elaboration of relevant constructs. Results: Analyses revealed one theme that captured participants’ detailed descriptions of their experience of worry and five themes that identified factors important for bringing worry episodes to a close: natural drift, distraction, interpersonal support, feeling better, and reality testing. Conclusions: Patients with persecutory delusions report worry being uncontrollable and distressing but are able to identify ways that a period of worry can stop. The present study suggests that building on individuals’ distraction techniques, reality testing ability and their social support network could be of benefit. Research is needed to identify the most effective means of bringing paranoid worries to an end.